COMMUNICATION STRATEGIES OF HIGH AND LOW ACHIEVERS: A CASE STUDY - Melissa Mel; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
This study is about communication strategies used by high and low achievers when they were doing the role plays in X elementary school. This study is to find out two research questions about the types of communication strategies and the differences and similarities in their use by high and low achievers. In order to answer the research questions, the writer uses Brown’s communication strategies (2007) as the main theory and Littlewood’s (1984) as the supporting theory. There are three findings: First, the high achievers used nine types of communication strategies and the low achievers used seven types of communication strategies. Second, the high achievers used a lot of different types of communication strategies, but their frequency of using them was lower than the low achievers. On the other hand, the low achievers used fewer types of communication strategies, but their frequency of using them was higher than the high achievers.